2005
DOI: 10.1677/joe.1.06227
|View full text |Cite
|
Sign up to set email alerts
|

Release and regulation of leptin, resistin and adiponectin from human placenta, fetal membranes, and maternal adipose tissue and skeletal muscle from normal and gestational diabetes mellitus-complicated pregnancies

Abstract: The aim of this study was to determine the release and regulation of leptin, resistin and adiponectin from human placenta and fetal membranes, and maternal subcutaneous adipose tissue and skeletal muscle obtained from normal and gestational diabetes mellitus (GDM)-complicated pregnancies at the time of Cesarean section. Tissue explants were incubated in the absence (basal control) or presence of 10 µg/ml lipopolysaccharide (LPS), 10, 20 or 40 ng/ml tumor necrosis factor-(TNF-), interleukin (IL)-6 and IL-8, 1 µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
184
6
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(214 citation statements)
references
References 63 publications
15
184
6
3
Order By: Relevance
“…28 Approximately, the same rate of release was seen by cut pieces of adipose tissue that did not contain enough lipid to float. 28 The view that the expression of adiponectin mRNA is restricted to mature adipocytes is clearly untenable in view of the present findings and the recent reports that adiponectin is synthesized and secreted by human osteoblasts, 10 human cardiomyocytes, 11 murine skeletal muscle, 12 human skeletal muscle and placenta, 13 human liver biopsies, 14 human placental synctiotrophoblasts, 15 as well as human fetal tissues of both mesodermal and ectodermal origin. 16 The present data using omental adipose tissue explants confirm the prior reports by Matsuzawa's laboratory that adiponectin release is reduced by obesity 4 as well as diabetes.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…28 Approximately, the same rate of release was seen by cut pieces of adipose tissue that did not contain enough lipid to float. 28 The view that the expression of adiponectin mRNA is restricted to mature adipocytes is clearly untenable in view of the present findings and the recent reports that adiponectin is synthesized and secreted by human osteoblasts, 10 human cardiomyocytes, 11 murine skeletal muscle, 12 human skeletal muscle and placenta, 13 human liver biopsies, 14 human placental synctiotrophoblasts, 15 as well as human fetal tissues of both mesodermal and ectodermal origin. 16 The present data using omental adipose tissue explants confirm the prior reports by Matsuzawa's laboratory that adiponectin release is reduced by obesity 4 as well as diabetes.…”
Section: Discussionmentioning
confidence: 64%
“…7,8 Adiponectin was originally described as an adipocytespecific protein. [1][2][3] However, more recently adiponectin mRNA and secretion have been demonstrated in boneforming cells, 9,10 cardiomyocytes, 11 skeletal muscle, 12,13 human liver, 14 human placental syncytiotrophoblasts 15 and human fetal tissues of mesodermic and ectodermal origin. 16 It is unclear whether tissues other than adipose tissue contribute to circulating levels of adiponectin that are some 40-fold higher than those of leptin in obese subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have further shown that the trophoblast and placenta are local sources of adiponectin expression. 55,56 In vitro tissue explant studies of human term placenta indicate that adiponectin can be secreted 57 and that it upregulates placental cytokine release. 58 Together, these studies strongly suggest paracrine effects of adiponectin in placental function.…”
Section: Effects Of Adiponectin On Reproduction and Fertilitymentioning
confidence: 99%
“…10 In human aortic endothelial cells, the cyclic AMP or protein kinase A pathway was evoked by adiponectin, 68,69 whereas in other endothelial cell models, the phosphoinositol kinase 3/protein kinase B (PKB) or Akt system transduces the adiponectin signal. 34 There is evidence for adiponectin activation of the peripheral peroxisome-activated receptor-g in placental tissue 57 and mitogen-activated protein kinase pathways in vascular tissue 70,71 and osteoblasts. 72 The recent discovery of interactions between the AdipoR1 and R2 and the adapter protein APPL1 28,29 has provided new insight into the mechanism by which adiponectin can act on target tissues.…”
Section: Mechanisms Of Action Of Adiponectin In Reproductive Tissuesmentioning
confidence: 99%
“…Another possible explanation for the reduced postpartum levels of adiponectin may be cessation of transport from the placenta. Although several investigators found placental expression of adiponectin, 26,27 others failed to find the placenta as a novel site for adiponectin expression. 28 Given the controversy in the literature, we cannot rule out this possibility.…”
Section: Commentmentioning
confidence: 99%